Identification of Microplastics in Three Fish Species in Tondano Lake, Minahasa, Indonesia - Fernando Andre Watung; Alva Sahiri Alexander Supit; Merry Triastuti Gosal (Advances in Tropical Biodiversity and Environmental Sciences, 2025)
Microplastic pollution is a significant threat to aquatic ecosystems and human health, particularly in Indonesia, a major contributor to plastic waste. This study investigated the presence and characteristics of microplastics in three commonly consumed fish species from Tondano Lake, North Sulawesi: mujair (Oreochromis mossambicus), payangka baru (Oxyeleotris marmorata), and payangka lama (Ophiocara poropechala). Analysis of gills and gastrointestinal tracts (GIT) from 11 fish samples revealed microplastic contamination in all species. Mujair exhibited the highest microplastic abundance, predominantly fragments in both gills and GIT. Payangka baru showed more fibers in the GIT and fragments in the gills, while payangka lama had more fibers in the GIT and fragments in the gills. A positive correlation was observed between fish body weight and microplastic accumulation in the GIT, but not the gills. The findings confirm microplastic contamination in Tondano Lake fish, highlighting the need for stricter waste management and further research on human health implications.